Desmoplastic Small Round Cell Tumors: A Case Series of a Rare Tumor and Literature Review - D. Harindran, Vallathol; Moideenkutty, Sajna Vengasseri; Kuni Thanseer, Neeliyath Thazha; Prashanth, Parameswaran; Warrier, Narayanankutty (Asian Pacific Journal of Cancer Care, 2023)
Background: Desmoplastic small round cell tumor (DSRCT) is a rare and aggressive malignancy that predominantly affects males. It typically arises in the abdominal cavity and is typically diagnosed through histopathological examination. Most cases of DSRCT exhibit a characteristic EWSR1-WT1 gene fusion. In this report, we present a series of 3 cases of DSRCT encountered at our institution. Case Presentation: All cases were diagnosed at an advanced stage, consistent with findings in previously available literature. Conclusion: The optimal treatment approach for DSRCT involves a multidisciplinary team. The standard chemotherapy regimen used is typically the Ewing’s sarcoma protocol of multiagent chemotherapy. Surgical interventions, such as cytoreduction and intraperitoneal hyperthermic chemotherapy, are the preferred procedures, although their feasibility is limited. Ongoing clinical trials investigating targeted therapies offer promising avenues for improving treatment outcomes and prognosis in DSRCT. DSRCT is a tumor associated with a poor prognosis. The development of novel treatment approaches is essential to enhance survival rates for patients with this disease.